Overview of current regional and local scale air quality modelling practices: Assessment and planning tools in the EU. Issue 65 (November 2016) - Thunis, P.; Miranda, A.; Baldasano, J.M.; Blond, N.; Douros, J.; Graff, A.; Janssen, S.; Juda-Rezler, K.; Karvosenoja, N.; Maffeis, G.; Martilli, A.; Rasoloharimahefa, M.; et al.
Highlights: The outcome of the APPRAISAL project are summarized with respect to the review of current integrated assessment modeling practices. The APPRAISAL project database populated with 59 contributions out of 13 countries is used as basis for the review. Differences between state of the art and current practices remain important in all fields, calling for an increased harmonization of modelling practices in the EU. Abstract: The 2008 European Air Quality Directive (AQD) (2008/50/EC) encourages the use of models in combination with monitoring in a range of applications. It also requires Member States to design appropriate air quality plans for zones where the air quality does not comply with the AQD limit values. In order to cope with these various elements, a wide range of different modeling methods have been developed and applied by EU Member States in the last decade to assess the effects of local and regional emission abatement policy options on air quality and human health. However, an overall review of the methodologies that are used in different countries to compile local and regional air quality plans has not been performed so far. Such a review has been the objective of the APPRAISAL EU FP7 project with the main goal to identify methodologies and their limitations and to propose possible key areas to be addressed by research and innovation on the basis of this review. To fulfill these objectives, a structured online database of methodologies has been developed in collaboration with experts involved in the design of air quality plans (AQP). The current work relies on the APPRAISAL database which currently totals 59 contributions from 13 Member States. In this paper we summarize the outcome of the APPRAISAL project with respect to the review of current Integrated Assessment Modeling practices.